Jewish Studies in the Digital Age - Margolis, Michelle; Levi, Amalia S.; Ezra, Daniel Stökl Ben; Rürup, Miriam; Zaagsma, Gerben (Studies in Digital History and Hermeneutics, 2022)
The digitisation boom of the last two decades, and the rapid advancement of digital tools to analyse data in myriad ways, have opened up new avenues for humanities research. This volume discusses how the so-called digital turn has affected the field of Jewish Studies, explores the current state of the art and probes how digital developments can be harnessed to address the specific questions, challenges and problems in the field.